State, difference, and diversity: toward a path of expanded democracy and gender equality - Rania Antonopoulos; Francisco Cos-Montiel (Levy Economics Institute of Bard College, 2007)
Should the state treat men and women in identical ways, or should it legislate and enforce policies that are aware of gender differences? In other words, should the state be gender-blind or gender-sensitive? Gender, ethnic, religious, sexual orientation, ideological, economic, political, and cultural dimensions represent diversity among citizens. This paper argues that if the goal of the state is to promote democratic participation for all, a distinction must be drawn between socioeconomic characteristics that signify difference and those that manifest inequalities. The former require a politics of acceptance and recognition and policies to match, while the latter necessitate interventions that remedy or remove structural elements that result in inequalities. The authors suggest that such a framework is useful in that it lends itself to a better understanding of gender-based asymmetries.
Keywords: H1; E61; I3; J16; 330; state; inequality; difference; citizenship; social exclusion; gender; poverty